2010
DOI: 10.1128/jb.01197-09
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Conserved Amino Acid Residues of the Salmonella σ S Chaperone Crl Involved in Crl-σ S Interactions

Abstract: Proteins that bind factors typically attenuate the function of the factor by restricting its access to the RNA polymerase (RNAP) core enzyme. An exception to this general rule is the Crl protein that binds the stationary-phase sigma factor S (RpoS) and enhances its affinity for the RNAP core enzyme, thereby increasing expression of S -dependent genes. Analyses of sequenced bacterial genomes revealed that crl is less widespread and less conserved at the sequence level than rpoS. Seventeen residues are conserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
49
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(55 citation statements)
references
References 54 publications
6
49
0
Order By: Relevance
“…Surface-exposed conserved residues identified from our BTH analyses are shown in teal, as are F53 and Y22, which were identified in a previous study (48). Residue E52 (labeled "hidden") is surface exposed but is not visible in this view.…”
Section: Structure Of P Mirabilis Crlmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface-exposed conserved residues identified from our BTH analyses are shown in teal, as are F53 and Y22, which were identified in a previous study (48). Residue E52 (labeled "hidden") is surface exposed but is not visible in this view.…”
Section: Structure Of P Mirabilis Crlmentioning
confidence: 99%
“…100% conserved were replaced with alanines (48). Four of the substitutions in that screen met our analysis criteria, namely, Y22A, R51A, E52A, and F53A.…”
Section: Structure Of P Mirabilis Crlmentioning
confidence: 99%
“…In this system, the T25-S and Crl-T18 hybrid proteins were shown to interact, yielding levels of ␤-galactosidase activity higher than those detected in negative controls (Fig. 4B) (28). We previously showed that the first 71 residues of S were not required for Crl binding since the T25- and Crl-T18 chimeras interacted efficiently (28 and Fig.…”
Section: G282 Is Located In a Flexible Loop In Region 4 Ofmentioning
confidence: 99%
“…Several factors (Rsd, 6S RNA, ppGpp, and DksA) indirectly increase S competitiveness by decreasing the ability of 70 to bind to E or by inhibiting E 70 activity (21). Furthermore, the nonconventional regulatory protein Crl increases the performance of S (14,28,35,37,39,40,46). Unlike classical regulators of transcription, Crl binds S instead of DNA (3,12), and the transient interaction of Crl with S increases the association rate of S to E (12), thereby facilitating RNAP holoenzyme E S formation (12,14,46).…”
mentioning
confidence: 99%
See 1 more Smart Citation